Pelatihan Peningkatan Pasing Bawah Bola Voli dengan Penerapan Metode VAK (Visualization, Auditory, Kinestetic) pada Siswa SMA Ahmad Yani - Ririn Dwi Agustin; Kenys fadhilah Zamzam; Choirul Kurniawan (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2025)
Volleyball underhand passing training is a process of coaching and developing volleyball players' skills through physical, technical, tactical, and mental exercises to improve performance in the game. This training can be conducted at various levels, from beginners to professionals, and covers several important aspects that support the improvement of basic skills. One of the basic techniques that must be mastered by players, especially in adolescence, is the underhand pass. This technique is the main foundation for controlling the ball and maintaining the continuity of the game. However, based on the results of initial observations on Ahmad Yani High School students, it was found that students' underhand passing ability is still relatively low. As many as 85% of students scored below average, indicating that they have difficulty mastering this basic technique. This problem presents a challenge in physical education learning, especially in volleyball. One contributing factor is the lack of variety and creativity in the teaching methods used by teachers, resulting in a lack of student motivation. This study aims to apply the VAK (Visual, Auditory, Kinesthetic) method in volleyball underhand passing training. The VAK method is a learning approach that combines three main learning styles: visual (sight), auditory (hearing), and kinesthetic (movement). This approach is believed to help students understand techniques more comprehensively, tailored to their individual learning styles. Integrating the VAK method into the training process is expected to significantly improve student learning outcomes, particularly in mastering volleyball underhand passing techniques. This research also aims to provide alternative, more innovative and effective learning strategies for physical education teachers in schools.